2020
DOI: 10.3390/healthcare8030246
|View full text |Cite
|
Sign up to set email alerts
|

A School Nurse Competency Framework for Continuing Education

Abstract: Background: This study develops a school nurse competency framework for continuing education based on focus group interviews and a literature review. Methods: This study uses a qualitative content analysis with 12 school nurses. Six school nurses verify the content validity for the competency framework for continuing education using the content validity index. Results: School nurse competencies are defined as the knowledge, skills, and attitudes required of school nurses to provide safe school nursing. Six cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Further, triage guidelines for schools have not yet been developed [10], and there is a lack of refresher training and continuing education for school nurses [10,30,31]. We found that the correlations between the Triage Competency Scale subdomains of Clinical Judgment and Expert Assessment and school nursing experience were the lowest in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Further, triage guidelines for schools have not yet been developed [10], and there is a lack of refresher training and continuing education for school nurses [10,30,31]. We found that the correlations between the Triage Competency Scale subdomains of Clinical Judgment and Expert Assessment and school nursing experience were the lowest in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Ongoing education for school nurses based on a theoretical framework is recommended. Yet there is a dearth of qualitative studies that identify the training needs of school nurses in competency-based education programs ( Shin & Roh, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing education for school nurses based on a theoretical framework is recommended. Yet there is a dearth of qualitative studies that identify the training needs of school nurses in competency-based education programs (Shin & Roh, 2020). In summary, different school nurse-led asthma interventions carried out in schools can improve child health outcomes.…”
Section: School Nurses' Training Needsmentioning
confidence: 99%
“…As they can be responsible for providing emergency nursing care in life threatening situations, school nurses find themselves experiencing role confusion due to an absence of legal protection from medical accidents [ 15 ]. Therefore, CE regarding T1DM-specific law in school settings is needed for school nurses so that they can practice nursing care according to proper legal and ethical principles [ 29 ].…”
Section: Discussionmentioning
confidence: 99%